Analisis Waste pada Line Production Liquid Produk Sucralfate PT X dengan Menggunakan Pendekatan Value Stream Mapping - Rahmatiin, Nisaa Fatwa; Rochman, Didit Damur (IAI Nasional Laa Roiba Bogor, 2025)
PT X is a pharmaceutical company that produces Sucralfate, an important pharmaceutical product requiring an efficient production process to meet market demand. This study aims to identify and address bottlenecks in the Sucralfate production line using Value Stream Mapping (VSM), Process Activity Mapping (PAM), and Waste Assessment Model (WAM) techniques. The Current State Map analysis reveals significant bottlenecks in the change over and documentation processes, primarily due to numerous Non-Value Added (NVA) activities. WAM identifies the primary waste as waiting, with a percentage of 26.30%, contributing to delays and increased lead time in production. To address these issues, several improvement suggestions have been formulated. For the dispensing stage, the implementation of an automated measurement system with integrated digital scales is proposed to enhance efficiency and accuracy. For the filling stage, it is recommended to replace the nozzle and add components to the hopper cap to reduce setup and repair time. The mixing process will also be optimized by adding an additional mixing tank and implementing batch campaigns to reduce waiting time between processes. Additionally, improvements to the documentation system by transitioning to a digital ERP-integrated system are proposed to accelerate QC verification and reduce waiting time. Although the Future State Map has not yet demonstrated a significant reduction in inventory or lead time, it is anticipated that the proposed improvements will significantly reduce NVA activities, leading to a positive impact on inventory reduction and increased efficiency in the Sucralfate production line at PT X.